A positive linear correlation between the triglyceride-glucose index and in-stent restenosis after percutaneous coronary intervention in patients with coronary heart disease - Mao, Jin; Fang, Zigen; Jiang, Shan; Xia, Zeyan (Frontiers in Cardiovascular Medicine, 2025)
AimsThe association between the triglyceride-glucose (TyG) index and in-stent restenosis (ISR) after percutaneous coronary intervention (PCI) in patients with coronary heart disease (CHD) remains inadequately explored. This study aimed to evaluate the relationship between TyG and ISR in patients with CHD following PCI.MethodsThis retrospective study included 519 patients with CHD undergoing PCI. TyG, considered as the exposure variable, was divided into lower (≤9.21) and higher (>9.21) groups based on the optimal cutoff determined by receiver operator characteristic (ROC) analysis, with ISR as the outcome variable. Multivariable logistic regression, subgroup analysis, ROC analysis and restricted cubic spline (RCS) modeling were used to assess the association between TyG and ISR.ResultsPatients with higher TyG had a significantly greater incidence of ISR compared to patients with lower TyG (P = 0.003). Patients with ISR had higher levels of TyG compared with patients without ISR (P = 0.006). In multivariable logistic regression analysis, after adjusting for confounding variables, a higher TyG index was significantly associated with an increased risk of ISR, both as a categorical and a continuous variable [Model 3, OR (95% CI), P value: 1.786 (1.134, 2.814), 0.012 and 1.408 (1.034, 1.917), 0.030, respectively]. The association remained significant in subgroups aged < 60 years, male, non-smokers, and those with hypertension (P < 0.05). Additionally, ROC analysis showed that TyG had modest predictive value for ISR (AUC = 0.571, P = 0.020), and its addition to the baseline model significantly improved the overall predictive performance (AUC = 0.643, P < 0.001). RCS analysis further confirmed a positive linear correlation between TyG and ISR (P = 0.042; P for nonlinearity = 0.808).ConclusionA higher TyG index is significantly associated with an increased risk of ISR in CHD after PCI, highlighting its potential as a valuable biomarker for cardiovascular risk stratification.